THE STATE OF INTEGRATED REPORTING IN MALAYSIA: A DESCRIPTIVE ANALYSIS OF DISCLOSURE PRACTICES - Wisaksono, Endhyta; Muhamad, Siti Fariha; Jamil, Amira (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
The practice of Integrated Reporting (IR) has been experiencing a strong momentum in Malaysian corporate environment, as can be seen by a significant increase of firms incorporated in the open market that have begun to utilize the practice. Although the spread of IR is instinctively well received, concern remains that diffusion is formidable on paper but wanting in substance, a kind of window dressing of the more surface and strategic conceptual transformation which would be required of actual integrated reporting. The next standard to fear is the level to which the disclosures go beyond professional formality to express the real professional integrated thinking. This paper aims at a descriptive, diagnostic mapping of current IR reporting of the Malaysian publicly listed firms. We theorize that our focus is to test the hypothesis of material, and not ritual, cognizance of strategic integration in the preparation of IR disclosure, determine whether or not motivation to observed practice arises due to substantive commitment in the practice or due to a compulsive regulatory and normative intensity. Our sample consists of 1,124 firm years that make up a balanced sample of 281 non-financial firms on the 2021 to 2024 reporting window on the Main Market of Bursa Malaysia. The quality of disclosure used is the evaluation of annual reports by a manual, professional focused analysis based on a self-constructed 36-item, IR Disclosure Index (IRDIN) meshing the dimensional expectations of the International Integrated Reporting Framework. Observance summaries of IR are presented in form of descriptive statistics whereas t-tests and one-way ANOVA are used to see the impact of formal covariates that are firm specific. In the research, disclosure was computed in aggregate with a figure of 40.6, which confirms that there is indeed a moderate, albeit lopsided, momentum throughout the reference period. An intense divergence in integrations took its toll: maturity and conformity-oriented items, such as Governance (75.2) and Performance (70.1) outperformed propensity-oriented and strategic items, which were manifested in Outlook (21.7) and Strategy and Resource Allocation (25.4) a significant timeslot. Analysis of the result gained revealed substantial diversity between sectors, and each disclosed differently. These results, taken together, provide a reasonable substantiation of the assumption that the implementation of Integrated Reporting in Malaysia is still young, as it involves the organization of procedurally developing documentation with the focus on formal instead of substantive compliance. The current trend, with its backwards accent to focus and obedience-driven reportages, does not focus on the prospective revelations that the IR framework should embrace. In order to take advantage of such a transformative promise of IR, firms should settle in a contracted, compliance form of the posture with a deliberate, programmed contravention, instead adopting the systemic subtext of integrated thinking of all the levels of organisational deliberation and practice.